Ambulance integration model in smart city for health services - Dewi, Rafiqa; Tulus, Tulus; Zarlis, Muhammad; Budhiarti Nababan, Erna (Bulletin of Electrical Engineering and Informatics, 2025)
Smart city is a city built to create efficient, sustainable, fair and livable cities. Increasing the percentage of population survival in standard and emergency times or emergency medical services (EMS) is one of the main pillars of a smart city. This study develops previous research. The weakness of this model is that it needs to consider the dynamic travel time factor. The model only considers the fixed travel time between two locations, which may not represent the actual conditions on the highway. It is less flexible because it only finds one threshold value α for all λi. Researchers succeeded in developing a model to overcome the model weaknesses in (4) by adding new constraints that consider ambulance capacity and overcome the shortcomings of the model (5) by adding tighter limits on the value of α to minimize the difference between the values of λi and αλi. In addition, constraints can also be added to ensure that α is a realistic value and meets business requirements.